SURİYELİLERİN SOSYO-DEMOGRAFİK ÖZELLİKLERİ İLE SUÇA KARIŞMA ORANLARI ARASINDAKİ İLİŞKİNİN İNCELENMESİ: BURDUR İLİ ÖRNEĞİ - Serkan Küçükdoğru (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In this study, the rate of involvement of Syrian individuals living in Burdur city depending on crime types will be examined. The profile of Syrians living in Burdur and the criminal orientation of Syrians depending on crime types will be evaluated from the data of Burdur Provincial Police Department. Therefore, the general proportion of Syrians as real persons in the incidents will be determined according to the crime types. Within the scope of the research, a crime type profile will be created for all foreign nationals living in Burdur. In the research, it will be examined whether there is a relationship between the socio-demographic characteristics of the Syrians and their tendency to crime. In this context, the educational status of Syrian refugees will be evaluated within the scope of primary, secondary and high school, and it will be examined whether it has an effect on the crime profile.